Global trends and emerging hotspots in neuromyelitis optica spectrum disorder diagnostic research - Siyu Lei; Yifeng Zhang; Yanqiang Wang (Medicine, 2026)
Background: Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune inflammatory disease of the central nervous system characterized by recurrent optic neuritis and longitudinally extensive transverse myelitis, frequently leading to severe and irreversible disability. Over the past decade, advances in diagnostic criteria, serological testing, and biomarker research have substantially transformed the diagnostic framework of NMOSD. However, a comprehensive bibliometric analysis focusing specifically on diagnostic research in this field has been lacking. Methods: Publications related to NMOSD diagnostic research published between 2016 and 2025 were retrieved from the Web of Science Core Collection. After refinement of the search strategy and manual screening based on predefined relevance criteria, bibliometric analyses were performed using CiteSpace, VOSviewer, and the Bibliometrix package in R to evaluate publication trends, international collaboration patterns, co-citation networks, and evolving research hotspots. Results: A total of 2029 publications were included. Annual publication output and citation counts increased steadily throughout the study period, reflecting sustained expansion of academic interest. China was the leading contributor, with strong collaborative links to the United States and the United Kingdom. The 2015 international consensus diagnostic criteria emerged as the most influential reference, serving as a foundational framework for subsequent research. Co-citation and keyword analyses demonstrated a clear shift from an early focus on disease definition and differential diagnosis toward biomarker-guided and technology-enabled precision diagnosis. Current research frontiers include optimization of aquaporin-4 immunoglobulin G detection platforms, astrocytic injury biomarkers such as glial fibrillary acidic protein, inflammatory mediators including interleukin-6 and complement components, magnetic resonance imaging– and optical coherence tomography–based neuroimaging markers, and multimodal diagnostic assessment. Conclusion: NMOSD diagnostic research has transitioned from consensus-driven classification toward integrated, multimodal precision strategies. Continued international collaboration and biomarker standardization will be essential to improve early diagnosis and clinical management.